Comprehensive Effect of Different Crop Loads on the ‘Shine Muscat’ Quality - Jianing LI; Yulin ZHANG; Tingting MA; Yulin FANG; Xiangyu SUN (Shipin gongye ke-ji, 2024)
To investigate the effects of different crop loads on the overall quality of 'Shine Muscat', this study was conducted to regulate the crop loads by berry thinning and to evaluate the sugar, acid and phenolic contents, antioxidant activity and economic benefits of the berries. The results showed that the average berry weight at low crop loads increased significantly, glucose and fructose contents increased significantly, and tartaric and malic acid contents decreased significantly, leading to a significant increase in the sugar-acid ratio of the berries (P<0.05). The phenolic content at low crop loads also increased significantly and the antioxidant capacity of the berries was significantly better than the other treatment groups (P<0.05). The excellent overall quality of berries at low crop loads made them more economically profitable. Thus, better grape quality could be achieved by precisely controlling the berry crop load.